Advances in clean energy : production and application - Anand, R. B., 1976-; Babu, B.; Thangarasu, Vinoth (Boca Raton, FL : CRC Press, 2021)
"This book endeavours to support sustainable clean energy technology and green fuel for clean combustion by reviewing the pros and cons of currently available technologies on biodiesel production from biomass sources, recent injection strategy, low-temperature combustion technology and biofuels derived from biomass sources. Discussed topics include overview of global energy sources and present energy scenario, biodiesel production techniques, the physico-chemical and thermal behavior of biodiesel, metal and alcohol additives on diesel engine combustion, novel advanced injection strategy, low-temperature combustion technology, lignocellulose biomass and conversion into biofuels"--
1. Global Energy Sources and Present Energy Scenario 2. Biodiesel Production Techniques -- The State Of The Art 3. Physicochemical and Thermal Properties of Biodiesel 4. Biodiesel and Additives on Diesel Engine Efficiency and Emission 5. Recent Advanced Injection Strategy on Biodiesel Combustion 6. Low Temperature Combustion Technology on Biodiesel Combustion 7. Solid Waste Management 8. Assessment of Physicochemical Properties and Analytical Characterization of Lignocellulosic Biomass 9. Lignocellulosic Biomass Conversion into 2nd and 3rd Generation Biofuels 10. The Microbiology Associated with Biogas Production Process 11. Current Status and Perspectives of Biogas Upgrading and Utilization
OCLC-licensed vendor bibliographic record.
Keywords: Renewable energy sources